2022
DOI: 10.1111/cns.13962
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma phosphorylated tau181 and neurofilament light chain with brain amyloid burden and cognition in objectively defined subtle cognitive decline patients

Abstract: Aims There is increasing evidence that plasma biomarkers are specific biomarkers for Alzheimer's disease (AD) pathology, but their potential utility in Obj‐SCD (objectively defined subtle cognitive decline) remains unclear. Methods A total of 234 subjects, including 65 with brain amyloid beta (Aβ) negative normal cognition (Aβ− NC), 58 with Aβ‐positive NC (Aβ+ NC), 63 with Aβ− Obj‐SCD, and 48 with Aβ+ Obj‐SCD were enrolled. Plasma Aβ42, Aβ40, Aβ42/Aβ40 ratio, phosphorylated tau181 (p‐tau181), neurofilament lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Some authors use cognitive composite scores to identify MNPD, 26,27 while other, frequently used criteria require low scores in a certain number of cognitive tests to classify someone as MNPD+. 11,24,36 In our sensitivity analyses, MNPD was a significant predictor of the progression to MCI and showed a similar pattern of results across all the applied MNPD criteria. This suggests that the clinical relevance of MNPD in patients with SCD does not depend on a specific operationalization of the construct.…”
Section: Discussionsupporting
confidence: 52%
“…Some authors use cognitive composite scores to identify MNPD, 26,27 while other, frequently used criteria require low scores in a certain number of cognitive tests to classify someone as MNPD+. 11,24,36 In our sensitivity analyses, MNPD was a significant predictor of the progression to MCI and showed a similar pattern of results across all the applied MNPD criteria. This suggests that the clinical relevance of MNPD in patients with SCD does not depend on a specific operationalization of the construct.…”
Section: Discussionsupporting
confidence: 52%
“…A novel aspect of the current study was a more thorough determination of cognitive function by using cognitive trajectories for each participant between 2015 and 2022 and estimating their cognitive test scores coincident with the 2018 serum NfL analysis. This contrasts with previous cross-sectional studies that have looked at single timepoint cognitive test scores coincident with blood NfL measures (Osborn et al, 2019;Huang et al, 2022). This study used cognitive data both preceding and succeeding the NfL analysis to determine participants cognitive test scores more accurately at the time of NfL analysis, rather than relying on a single timepoint test score.…”
Section: Discussionmentioning
confidence: 93%
“…When looking at the cross-sectional relationship between blood NfL and cognition, a study by Osbourn et al found that higher plasma NfL was not associated with performance across multiple cognitive domains in unimpaired participants between the ages of 60 and 92 years (Osborn et al, 2019). In contrast to this, a more recent crosssectional analysis in participants over 50 years of age, with normal cognition or objectively defined subtle cognitive impairment (Obj-SCD), showed that higher NfL levels were associated with lower global cognition, verbal episodic memory, visual episodic memory and executive function (Huang et al, 2022). However, when looking at subgroup analyses based on cognition (normal and Obj-SCD) and brain amyloid beta (Aβ+ and Aβ−) status there were differing results; NfL had a negative correlation with verbal episodic memory in the Aβ− normal cognition and Aβ− Obj-SCD groups, and a negative association with MMSE in the Aβ+ normal cognition group (Huang et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…This correlation was strongest among participants with Clinical Dementia Rating scores of 1 or more. A retrospective study involving 404 participants from three independent cohorts, and a cross‐sectional analysis of 243 participants, found that elevated plasma p‐tau181 concentrations were associated with poorer performance across multiple cognitive assessments in AD/MCI patients, particularly those who were Aβ positive 22,23 . Blood p‐tau181 concentrations may begin to increase decades before the deposition of tau aggregates and onset of AD clinical features 24 .…”
Section: Discussionmentioning
confidence: 99%